(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
We know that any living organism is in close contact with the external environment. Examples include temperature, humidity, light, nutrient environment, concentration, symbiosis and antagonism between microorganisms. This article describes the effect of the above factors on the vital activity of microorganisms.